Social media and internet use for anti-tobacco health promotion toward adolescent and youth in Asia : a systematic review - Agung Anugerah; Ashandi Triyoga Prawira (BKM Public Health and Community Medicine, 2021)
Objective: This study explores the strategy of social media and internet use for anti-tobacco health promotion targeted for adolescent and youth in Asia Method: We performed a literature search of articles in the last 10 years using PubMed with keyword as follows : (social media OR internet) AND (tobacco OR smoking) AND (teen* OR youth OR adolescent OR children OR school age) AND (asia). Critical appraisal was done using PRISMA-P 2015 checklist. Results: A total of 209 articles were screened and 7 studies included, 5 studies focused on social media/internet effectiveness on anti-tobacco promotion and 2 studies focused on the demographic feature. The Effectiveness of social media is shown positively correlated with anti-tobacco knowledge and attitude throughout all 5 studies with various results. Social media and the internet is an effective means as adolescents and youth in Asia tend to use these media rather than a more conventional media for health information, tobacco prevention included. The adolescent and youth are less likely to find anti-tobacco messages in their social media or internet use because these messages tend to be more concentrated in conventional media. In contrast to that, tobacco companies advertising is more commonly found on social media and the internet, therefore its exposure becomes a significant factor in influencing adolescent smoking initiation. Conclusion: Taken together, these evidence show consistent benefit of social media and internet use in promoting anti-tobacco messages among adolescents and youth in Asia. Holistic framework (including family support, smoke free school, etc) to gain tobacco prevention or cessation among adolescents must incorporate social media and internet use for campaigns to raise awareness and attitude. An understanding of the adolescent smoking initiation is compulsory in creating a tailor made message that fits their context.